ANALISIS BRAND TRUST, BRAND IMAGE, DAN BRAND LOYALTY TERHADAP KEPUTUSAN PEMBELIAN NIPPONPARTS PADA CV.MOTOROLI - Berry Wibowo; Sudarwati Sudarwati; Ida Aryati (Politeknik Negeri Lhokseumawe, 2023)
The study of this study was to further examine the simultaneous and partial effects of brand trust, brand image, and brand loyalty on buying decisions for Nipponparts at CV.Motoroli. Using a quantitative method with Nipponparts buyers at CV. Motoroli was used as a population and taking acsamplecofc100crespondents. Thecsamplingctechnique iscpurposivecsampling, reinforced by simultaneous tests, partial tests, multiple linear regression tests, and coefficientcofcdeterminationctests. Thecresultscshowedcthatcthe 3 independent variables hadcacpositivecandcsignificantceffectconcthe dependent variable. The research tool uses the SPSS Statistics 25 program. Keywords: Brand Trust, Brand Image, Brand Loyalty, Buying Decision.